Impact of Latin-American and Caribbean antidumping measures on Chinese exports - Yan Zhang (Inter-American Development Bank (IDB), 2017)
This paper uses customs transaction data covering all Chinese exporters and the World Bank's antidumping database to investigate how they responded to Latin-American and Caribbean (LAC) antidumping measures during 2000-2012 period. The paper uses the difference-in-differences identification strategy, and finds a substantial trade-dampening effect of these measures at the product level which operates through the intensive margin (i.e., a decrease in export volume per exporter) rather than the extensive margin (i.e., a decrease in the number of exporters) on average. Although we do not find a significant extensive margin effect, we still observe a positive number of exporters exited the LAC market after antidumping measures, specifically, less productive firms and trade intermediaries are more likely to exit the market. The pattern of Chinese exporters exiting the protected market was the same in ARG, BRA, MEX and COL. The antidumping measures taken by different countries had different impacts on Chinese exporters. MEX and BRA antidumping measures not only had an intensive margin but also an extensive margin effect on Chinese exports. ARG antidumping measures only had an intensive margin effect. COL antidumping measures had no effect. The paper also finds that MEX antidumping measures caused a significant increase in the export prices of the affected Chinese products, but no significant increase in the export prices for the other three countries. The paper does not find any shift in the destinations of the affected Chinese exports.
Keywords: F13; D22; F14; L25; 330; Antidumping investigations; Difference-in-differences estimation; Extensive and intensive margins; Trade deflection